OPTIMIZATION OF THERAPY FOR GASTROESOPHAGEAL REFLUX DISEASE IN COMORBIDITY WITH FUNCTIONAL DYSPEPSIA - Mirvosit M. Karimov; Pulat S. Zufarov; Guzal N. Sobirova; Shahlo S. Aripdjanova; Dildora K. Karimova (Central Asian Journal of Medicine, 2023)
It has been shown that in patients with GERD and functional dyspepsia, the use of proton pump inhibitors leads to a decrease in heartburn and pain behind the sternum. However, symptoms such as regurgitation, belching, feeling of early satiety and heaviness after eating were stopped ineffectively. The inclusion in the treatment complex of the prokinetic domperidone at a dose of 10 mg 3 times a day contributed to a more effective regression of symptoms of impaired motility of the esophagus and stomach.